Peripheral Blood Smear and RBC Histogram in Anemia: A Two-Year Observational Study - Harshul Patidar; Uditkumar Agrawal; Sonu Rawat; Nisha Rohit (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2023)
In our geographic region, anemia is a prevalent medical condition, and our study focuses on the use of comprehensive hematological parameters, including the RBC Histogram and peripheral blood smears, as an initial diagnostic approach to promptly identify and enhance cost-effectiveness in anemia diagnosis. The aim of our study is to elucidate the correlation between the RBC Histogram and Peripheral Blood Smear analyses in diagnosing anemia. We examined 200 subjects, utilizing a 5-part Fully Automated Hematology Analyzer for CBC assessments and employing Field's staining technique for peripheral blood smears. Among the 200 anemia cases, 62% presented with Microcytic Hypochromic Anemia, 4.5% with Macrocytic Anemia, 16.5% with Normocytic Normochromic Anemia, 7.5% with Dimorphic Anemia, 7% with Hemolytic Anemia, and 2.5% with Pancytopenia. Microcytic Hypochromic Anemia cases displayed a leftward shift in the RBC Histogram, while Macrocytic Anemia cases exhibited a pronounced rightward shift. Hemolytic Anemia cases were characterized by either a broad-based or bimodal peak in the histogram. In conclusion, the combined use of RBC Histogram analysis and peripheral blood smear scrutiny is a highly valuable diagnostic tool for a spectrum of hematological disorders, with Fully Automated Hematology Analyzers proving beneficial and dependable for peripheral smear evaluation.